The Role of Financial Technology Use and Women Entrepreneur Empowerment in Developing Entrepreneurial Competence and Business Performance of MSMEs in Medan City - Sairun, Aryani; Aristantya, Selvi; Amril, Amril; Lubis, Irna Triannur (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyse the influence of Women Entrepreneurs Empowerment and the Use of Financial Technology on Business Performance and the Development of Entrepreneurial Competence in MSMEs. The research method used is quantitative with data collection through questionnaires distributed to MSME actors, then analysed using linear regression. The results show that women's empowerment has a significant effect on business performance and entrepreneurial competency development, while the use of financial technology has a significant effect on business performance but no effect on entrepreneurial competency development. These findings emphasise the importance of women's empowerment as a key strategy in improving entrepreneurial skills and business performance, as well as the need for the appropriate use of financial technology to support business performance. This study has implications for MSME actors, the government, and related institutions in designing training programmes, mentoring, and digital facilities to increase women's empowerment and the effective use of financial technology in the MSME sector.